The effect of oxygen transfer mechanism on the cathode performance based on proton-conducting solid oxide fuel cells. Issue 5 (12th December 2014) - Hou, Jie; Qian, Jing; Bi, Lei; Gong, Zheng; Peng, Ranran; Liu, Wei
Abstract : Two different types of proton-blocking composite cathode materials with different oxygen transfer mechanisms used for H-SOFCs were evaluated for the first time. Abstract : Two types of proton-blocking composites, La2 NiO4+ δ –LaNi0.6 Fe0.4 O3− δ (LNO–LNF) and Sm0.2 Ce0.8 O2− δ –LaNi0.6 Fe0.4 O3− δ (SDC–LNF), were evaluated as cathode materials for proton-conducting solid oxide fuel cells (H-SOFCs) based on the BaZr0.1 Ce0.7 Y0.2 O3− δ (BZCY) electrolyte, in order to compare and investigate the influence of two different oxygen transfer mechanism on the performance of the cathode for H-SOFCs. The X-ray diffraction (XRD) results showed that the chemical compatibility of the components in both compounds was excellent up to 1000 °C. Electrochemical studies revealed that LNO–LNF showed lower area specific polarization resistances in symmetrical cells and better electrochemical performance in single cell tests. The single cell with LNO–LNF cathode generated remarkable higher maximum power densities (MPDs) and lower interfacial polarization resistances ( R p ) than that with SDC–LNF cathode. Correspondingly, the MPDs of the single cell with the LNO–LNF cathode were 490, 364, 266, 180 mW cm −2 and the R p were 0.103, 0.279, 0.587, 1.367 Ω cm 2 at 700, 650, 600 and 550 °C, respectively. Moreover, after the single cell with LNO–LNF cathode optimized with an anode functional layer (AFL) between the anode and electrolyte, the power outputs reached 708 mW cm −2 at 700 °C. These results demonstrate that the LNO–LNF composite cathode with the interstitial oxygen transfer mechanism is a more preferable alternative for H-SOFCs than SDC–LNF composite cathode with the oxygen vacancy transfer mechanism.